KENDALA IMPLEMENTASI PEMBERIAN PESANGON DALAM KONDISI PERUSAHAAN YANG DITUTUP TERHADAP PEKERJA YANG DIKENAKAN PHK : STUDI KASUS PUTUSAN Nomor 183/Pdt.Sus-PHI/2017/PN.Mdn - Widiya Dwi Novarianti; Arya Putra Wisnuwardhana; Oktavia Diva Ramadhani; Muhammad Syafri Qodri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Termination of employment (PHK) is often a complex issue, especially when a company is closed due to losses or liquidation. Based on Government Regulation (PP) Number 35 of 2021, workers affected by layoffs are entitled to receive compensation including severance pay, long service pay and compensation for rights. However, the implementation of granting these rights often faces obstacles when the company concerned has stopped operating. This research aims to examine the provisions for providing severance pay in situations where the company is closed according to PP 35 of 2021 and analyze the obstacles that occur in the case of Decision Number 183/Pdt. Sus-PHI/2017/PN.Mdn. Based on this case study, various obstacles were found, such as the company's inability to fulfill its obligations due to limited assets, legal uncertainty in resolving disputes, and time-consuming legal processes. This condition exacerbates uncertainty for workers who have lost their livelihoods. Through this research, it is concluded that although legal regulations have provided a clear basis regarding workers' rights, practical challenges in implementation still require serious attention. It is hoped that this study can provide recommendations for stakeholders to create more effective and fair mechanisms in resolving similar employment conflicts.